2020
DOI: 10.3390/md18060335
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Counteracts Excitotoxicity and Reduces the Ensuing Increases in Calcium Levels and Mitochondrial Reactive Oxygen Species Generation

Abstract: Astaxanthin (ASX) is a carotenoid pigment with strong antioxidant properties. We have reported previously that ASX protects neurons from the noxious effects of amyloid-β peptide oligomers, which promote excessive mitochondrial reactive oxygen species (mROS) production and induce a sustained increase in cytoplasmic Ca2+ concentration. These properties make ASX a promising therapeutic agent against pathological conditions that entail oxidative and Ca2+ dysregulation. Here, we studied whether ASX protects neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…It was reported that excessive mitochondrial ROS could induce a sustained increase of [Ca 2+ ] i . And antioxidants could prevent the increase of [Ca 2+ ] i and attenuated NMDA-induced neuronal damage [ 43 ]. Moreover, oxidative stress is also reported to lead to an increase of [Ca 2+ ] i released from the endoplasmic reticulum (ER) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that excessive mitochondrial ROS could induce a sustained increase of [Ca 2+ ] i . And antioxidants could prevent the increase of [Ca 2+ ] i and attenuated NMDA-induced neuronal damage [ 43 ]. Moreover, oxidative stress is also reported to lead to an increase of [Ca 2+ ] i released from the endoplasmic reticulum (ER) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress disturbs intracellular Ca 2+ homeostasis, resulting in excessive Ca 2+ efflux from the endoplasmic reticulum and an influx into mitochondria, which subsequently triggers mitochondrial membrane permeabilization, loss of mitochondrial membrane potential, and the release of mitochondrial pro-apoptotic factors [ 81 ]. It has been widely reported that AX prevents the ROS-induced Ca 2+ influx into mitochondria, protects against mitochondrial dysfunction, and inhibits apoptosis [ 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The role of AX in modulating mitochondrial-mediated activation of apoptosis is beyond the scope of this review.…”
Section: Mechanism By Which Astaxanthin Enhances Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…The receptors of adiponectin are AdipoR1 and AdipoR2, which are expressed at different levels in different tissues, and are involved in the regulation of glucose and fatty acid metabolism, mainly through the activation of Ca 2+ signaling, AMPK/SIRT1, and PPARα signaling pathways [ 165 ]. It has been reported that AX has an inhibitory effect on Ca 2+ signaling, which is mainly involved in ROS [ 83 , 85 , 86 , 87 , 88 ], but its effect on Ca 2+ /calmodulin-dependent protein kinase β (CaMKKβ), which is involved in the activation of AMPK [ 166 ] is still unknown. Thus, to summarize what is currently known, oxidative stress decreases the amount of adiponectin and its receptors.…”
Section: Mechanism By Which Astaxanthin Enhances Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…This interaction results in the disruption of cell membranes, compromising its ability to maintain cellular homeostasis, and promoting two important early biochemical changes. The first is the uncontrolled increase in cytosolic calcium (Ca 2+ ) levels flowing from the extracellular space into the cytosol [7][8][9][10][11][12][13][14], and the second is the accumulation of reactive oxygen species (ROS) [10,11,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Other Ca 2+ channels that seem to be involved in the Aβ-induced flux of Ca 2+ ions are the transient receptor potential melastatin 2 (TRPM2) [23], the voltage-dependent Ca 2+ channels (VDCCs) [24], and the transient receptor potential A1 (TRPA1) [25]. Another relevant early biochemical change resulting from the interaction of Aβ oligomers with cell membranes is oxidative stress, which is associated with the accumulation of ROS in the cytosol [10,11,15,16] and represents an important determinant in AD pathogenesis [26,27]. The elevation of ROS is caused by the activation of the oxidative metabolism to respond to the intracellular Ca 2+ increase induced by the oligomers and the consequent increased need for ATP by the Ca 2+ pumps, that try to restore the normal levels of intracellular Ca 2+ [10,28].…”
Section: Introductionmentioning
confidence: 99%